Efektivitas Rancangan 90 Hari Gratitude Journaling Terhadap Psychological Well-being dan Workplace Well-being Pada Dosen - T. M. Adriansyah; T. Elfira Rahmayati; Siti Annisa Rizki; Enika Diana Batubara; Yenni Ramadhani Harahap (Mahesa Research Center, 2026)
This study aims to determine the effectiveness of a 90-day gratitute journaling on psychological well-being and workplace well-being among lecturers in Medan. The study used a pre-experimental One-group pretest-posttest design with a gratitude journaling treatment for 90 days. Psychological well-being was measured using the PERMA Profiler instrument and workplace well-being through a workplace well-being questionnaire developed by Hyett & Parker. The study population was private lecturers in Medan. Sampling was conducted using nonprobability with criteria of being 33–56 years old, having worked for more than 2 years, having moderate stress levels, and being willing to participate in a 90-day gratitude writing training. The study sample consisted of 30 people. The study was analyzed quantitatively using paired tests and effectiveness tests (NGain scores). The results obtained a sig value of 0.003 for psychological well-being and 0.000 for workplace well-being, which means it is smaller than 0.05, indicating a difference in the values of psychological well-being and workplace well-being before and after the 90-day Gratitute journaling. Based on the average value of the pre-test and post-test, it shows that the research hypothesis is accepted, namely that there is a difference in the value of psychological well-being and well-being in the workplace before and after the 90-day gratitude journaling method was given to lecturers, but the results of measuring the effectiveness of the treatment showed a g value <0.3, which means it has low effectiveness.